The prosody of correction and contrast - Stavropoulou, P; Baltazani, M (Elsevier, 2020)
In the extensive literature on the prosodic expression of Information Structure (IS) the notion of contrast is typically coarse grained and subsumed under relational dichotomies like the theme-rheme or topic-focus, or as an inherent feature of focus, evoking a set of alternatives. This paper has two goals. First, we advocate for a more nuanced conception of contrast. This distinguishes between the “alternatives” based meaning of contrast on one hand and correction on the other, which is a more discourse-oriented meaning that encodes the speaker's assumptions about the hearer's beliefs. Second, we present experimental evidence that among the pragmatic types of contrast examined, only correction receives distinct prosodic marking, which cuts across the traditional IS topic-focus division and is realized in the same way in focus and topic constituents.